Optimization of Temperature and Time of Ultrasonic-Assisted Extraction Method on Flavonoid and Antioxidant Activity of Brown Rice from Demak, Indonesia - Susiloningrum, Dwi; Karimah, Nailatul; Handayani, Yanulia; Ismah, Kadar; Ruas, Adilson Castro; Xavier, Felipe (Journal of Islamic Pharmacy, 2024)
Brown rice contains a number of bioactive components, such as pigments and flavonoids, which act as antioxidant. Plants widely distribute polar flavonoid compounds, which actively function as antioxidant. Antioxidants are substances that can significantly inhibit or prevent the oxidation of the substrate. The body requires antioxidants to defend itself against attacks by free radicals. The goal of this study was to find the best temperature and time for the Ultrasonic-Assisted Extraction (UAE) method to measure the antioxidant activity and flavonoids in brown rice extract using UV-Visible spectrophotometry. The extract was prepared using the UAE method with 96% ethanol solvent at 45°C and 55°C for 20–30 minutes. Data obtained was statistically analyzed using the one-way ANOVA test. The study found that brown rice extracted with 96% ethanol at 45°C for 20 minutes produced 4.089 mg QE (Quercetin Equivalent)/g of total flavonoids. The antioxidant activity was the lowest, with an IC50 value of 381.102 ppm. The statistical analysis using the one-way ANOVA test revealed that there were no differences in temperature or time optimization that affected the levels of flavonoids and antioxidants. It can be concluded that the 96% ethanol extract of brown rice has the best flavonoid and antioxidant content. The best treatment was at 45°C and 20 minutes of extraction time.